Abrupt change of Antarctic moisture origin at the end of termination II - Masson Delmotte V.; Blunier T.; Cattani O.; Chappellaz J.; Cheng H.; Dreyfus G.; Edwards R. L.; Falourd S.; Govin A.; Kawamura K.; Johnsen S. J.; Jouzel J.; et al. (Proceedings of the National Academy of Sciences, 2010)
The deuterium excess of polar ice cores documents past changes in evaporation conditions and moisture origin. New data obtained from the European Project for Ice Coring in Antarctica Dome C East Antarctic ice core provide new insights on the sequence of events involved in Termination II, the transition between the penultimate glacial and interglacial periods. This termination is marked by a north–south seesaw behavior, with first a slow methane concentration rise associated with a strong Antarctic temperature warming and a slow deuterium excess rise. This first step is followed by an abrupt north Atlantic warming, an abrupt resumption of the East Asian summer monsoon, a sharp methane rise, and a CO2 overshoot, which coincide within dating uncertainties with the end of Antarctic optimum. Here, we show that this second phase is marked by a very sharp Dome C centennial deuterium excess rise, revealing abrupt reorganization of atmospheric circulation in the southern Indian Ocean sector.